Ancient glass: an interdisciplinary exploration - Henderson, Julian (Cambridge Univ. Press, 2013)
"This book provides an integrated interdisciplinary approach to the study of a complex and fascinating ancient material. A variety of aspects of ancient glass is discussed including principally archaeology, history, chemical analysis, materials science, geology and botany. The aims of the book are to explore these aspects by using a combination of focused studies and case studies in a variety of ancient and historical periods. Each case study, in Bronze Age Mesopotamia, Late Hellenistic-early Roman Middle East and the Islamic world, has been selected so as to incorporate contrasting social, political, economic and ritual contexts in which glass was manufactured, traded and used. These contrasting characteristics of societies therefore influenced the ways in which glass fitted into society: the ways in which it was manufactured and used. The relationships between production, trade and use of ancient materials including glass are complex. The scale of production involving a range of facilities and critical combinations of raw materials from a variety of sources were characteristic of the specific society and their ideologies. Each step in the chan̋e oppřatoire involved decisions, each with a social impact and significance leading to the manufacture of glass artefacts characteristic of that society. The control over each aspect of production was a reflection of the degree of social hierarchy, (perhaps involving social elites) and complexity at the time"--